Poleiros artificiais como núcleos de dispersão de sementes e fatores que influenciam este processo em área de cerrado sensu stricto no Triângulo Mineiro - Ferreira, Giancarlo Ângelo (2014)
Vertical artificial structures can attract and function as artificial perches, increasing seed rain. This perches can be a low cost method to restoration allowing a direct effect rather a random, as in natural processes. This work aims to verify the efficiency of different types of artificial perches as seed dispersal nuclei and the factors that influences these process. The study were conducted in a cerrado sensu stricto area in natural regeneration process belonging to Duratex S.A in Triângulo Mineiro, Brazil. There were installed three types of artificial perches (X, 3X and Wire) and they were monitored over a year. The data registered were the species of birds that used the perches, the species of plants present in seed rain, through the fecal samples under the perches and analizes the influence of temperature, rainfall and seasonality. Fruiting phenologies were realized in the plants. The efficiency of the artificial perches were measured through the comparison with the seed rain of the natural perches (control). In 200 hours of observation were registered 760 individuals of 24 birds species in the artificial perches. Were collected 607 fecal samples with 5480 seeds, being 569 samples under the artificial perches (5252 seeds) and 38 samples (228 seeds) under the naturals. The seeds were of 21 species/morphospecies of plants. The 3X perches were the most used by birds (p<0,05), however the seed rain didn‟t differ in relation to the X perches. The artificial perches were efficient, because they had a bigger number of seeds dispersed in relation to the natural perches (p<0,05). The mean monthly rainfall (mm) influenced positively the number of seeds dispersed under the perches and the number of birds in the perches, which was also influenced by the mean monthly temperature (ºC). There were a bigger number of birds registered in the perches during the rainy season (p<0,05), being the omnivorous the main guild, highlighting Cyanocorax cristatellus. The Miconia genus were the most represented in the phenology and in the seed rain. The artificial perches were efficient as seed dispersal nuclei and should be used to accelerate the regeneration of degraded areas. We highlight the omnivorous birds species and Miconia genus, because they were main groups that contributed to the seed dispersal in the study area. Researches that focus on the structure of artificial perches and the factors that may influence the seed rain under the perches deserve a special attention, because they can define strategies more directed and more efficient in the process of environmental restoration.